2005
DOI: 10.1007/bf03022059
|View full text |Cite
|
Sign up to set email alerts
|

Long current impulses may be required for nerve stimulation in patients with ischemic pain

Abstract: Purpose: To report on the efficacy of peripheral plexus catheters in the treatment of ischemic pain in spite of nerve stimulation with long current impulses. Clinical features:Two patients with severe neuropathic ischemic foot pain are described. A 56-yr-old man with diabetes, renal failure, and autonomic neuropathy presented with severe ischemic foot pain. Opioids produced excess sedation and hypotension. A 62-yr-old woman was admitted after femoralpopliteal bypass and developed a reperfusion pain syndrome no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 11 publications
2
8
0
2
Order By: Relevance
“…Use of higher current (> 1 mA) and a longer stimulation duration (> 0.3 msec) is recommended in these situations, but does not guarantee a successful block. 26 it has been suggested that local anesthetics may have an exaggerated effect on the spinal cord in the presence of demylination, 27 although this has not been confirmed in relation to peripheral nerve blocks. The patient described in case 1 had a chest wall deformity, and a good spread of local anesthetic around the axillary artery, was seen with a smaller volume requirement of local anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…Use of higher current (> 1 mA) and a longer stimulation duration (> 0.3 msec) is recommended in these situations, but does not guarantee a successful block. 26 it has been suggested that local anesthetics may have an exaggerated effect on the spinal cord in the presence of demylination, 27 although this has not been confirmed in relation to peripheral nerve blocks. The patient described in case 1 had a chest wall deformity, and a good spread of local anesthetic around the axillary artery, was seen with a smaller volume requirement of local anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…26 Only a few case reports have been published that describe difficulties in identifying the sciatic nerve in diabetic patients by electrical nerve stimulation. [10][11][12] Sites et al 9 reported on two patients with ultrasound-guided popliteal fossa blocks who required a minimum current of 2.4 and 2.6 mA, respectively, to elicit a motor response of the sciatic nerve. Other authors, however, performed sciatic nerve blocks in diabetic patients and were obviously successful in localising the nerve by electrical stimulation, although the stimulation threshold was not reported.…”
Section: Observed This Phenomenon In Sevenmentioning
confidence: 98%
“…Only a few case reports have been published indicating an alteration of the motor response of the sciatic nerve to electrical stimulation in patients at risk of peripheral neuropathy. [9][10][11][12] A systematic evaluation as to whether the electrical stimulation threshold for a motor response of the sciatic nerve is substantially increased in diabetic patients has not been carried out before. Eur J Anaesthesiol 2013; 30:435-440 Diabetic foot disease is a potentially disabling and lifethreatening complication that affects up to 25% of patients with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Grant and Coventry may seem more logical than the "modus operandi" I suggested, before writing the editorial, I looked at the published randomized studies of multiple-injection axillary block. In addition to my own studies (Koscielniak-Nielsen ZJ et al 1997, 1998, 1999ϫ 2, 2000, 2001, 2002, 2004, 2005 The nerve blocking sequence proposed by Drs. Grant and Coventry was used in 1 study (2001).…”
Section: Reply To Drs Grant and Coventrymentioning
confidence: 77%